2006
DOI: 10.1111/j.1471-4159.2006.03995.x
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW: Pin1 in Alzheimer's disease

Abstract: Proteolytic processing and phosphorylation of amyloid precursor protein (APP), and hyperphosphorylation of tau protein, have been shown to be increased in Alzheimer's disease (AD) brains, leading to increased production of b-amyloid (Ab) peptides and neurofibrillary tangles, respectively. These observations suggest that phosphorylation events are critical to the understanding of the pathogenesis and treatment of this devastating disease. Pin-1, one of the peptidyl-prolyl isomerases (PPIase), catalyzes the isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 153 publications
(332 reference statements)
3
137
1
8
Order By: Relevance
“…In AD brain, Pin1 is found to be colocalized with phosphorylated tau and also shows an inverse relationship to the expression of tau in AD brains (196,316). Further, Pin1 was also identified by redox proteomics as oxidatively modified protein in AD hippocampus (65,363). Oxidation and decreased levels and activity of this protein could favor the formation of NFTs, SP, and subsequent synapse or cell loss due to cell arrest (20).…”
Section: Identification Of Carbonylated Proteins In Brainmentioning
confidence: 98%
See 2 more Smart Citations
“…In AD brain, Pin1 is found to be colocalized with phosphorylated tau and also shows an inverse relationship to the expression of tau in AD brains (196,316). Further, Pin1 was also identified by redox proteomics as oxidatively modified protein in AD hippocampus (65,363). Oxidation and decreased levels and activity of this protein could favor the formation of NFTs, SP, and subsequent synapse or cell loss due to cell arrest (20).…”
Section: Identification Of Carbonylated Proteins In Brainmentioning
confidence: 98%
“…After this study, a number of other targets of oxidation have been reported from our laboratory in different brain regions, and these studies also showed that oxidatively modified proteins are prone to inactivation (80,368,369). Brain from subjects with amnestic mild cognitive impairment (MCI) showed increased levels of PCO compared with the age-matched controls (10,65,76,222). Further, global OS measurements revealed significantly higher levels of PCO in the MCI IPL relative to preclinical AD (PCAD) (and controls), despite equal levels of neuropathology (10).…”
Section: Application Of Redox Proteomics To Selected Neurodegenermentioning
confidence: 99%
See 1 more Smart Citation
“…Cys 113 was found to be sensitive to oxidation by increased reactive oxygen species found in AD patients thereby losing the protein's catalytic activity upon tau protein (Sultana et al, 2006;Chen et al, 2015;Innes et al, 2015). In summary, all events leading to a down-regulation of Pin1 in brain boost the likelihood of AD onset (Butterfield et al, 2006). Despite Pin1 up-regulation processes delay AD onset (Ma et al, 2012) they may increase the risk and early onset of frontotemporal atrophy (Lim et al, 2008;Ferri et al, 2016).…”
Section: Pin1 Is Involved In Dementia and Neuronal Diseasesmentioning
confidence: 99%
“…Cis p-tau was found to be a precursor of tau pathology and an early driver of neurodegeneration in AD. Pin1 protects against tau-aggregation by isomerizing p-tau and (Butterfield et al, 2006) by regulating tau dephosphorylation (Lu et al, 1999a. Pin1 also slows down the amyloidogenic Aβ production from amyloid precursor protein (APP) (Pastorino et al, 2006).…”
Section: Pin1 Is Involved In Dementia and Neuronal Diseasesmentioning
confidence: 99%